2020
DOI: 10.26848/rbgf.v13.6.p2908-2928
|View full text |Cite
|
Sign up to set email alerts
|

Achatina fulica na zona rural de Maringá, Paraná: relações ambientais

Abstract: O objetivo da pesquisa é avaliar a distribuição espacial do molusco Achatina fulica, espécie exótica, na zona rural do município. Para caracterizar e explicar a ocorrência positiva da espécie foram avaliados os seguintes elementos: localização em coordenada, temperatura, umidade, insolação, altitude e avaliação da arborização/cobertura vegetal. Em campo, foram detectados 40 propriedades rurais que possuem a espécie exótica, dispersa nas proximidades das residências, barracões, e não em meio às culturas temporá… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…According to Silva et al (2020), the presence of the Giant African snail has been reported in different environments, such as forests, capoeiras, caatingas, savannas, plantations, vegetable gardens, as well as in urban areas. In the Amazon, surveys show that its presence may be associated with the transport of this mollusc in accidental loads, denoting in an alert situation due to its high dispersal capacity, diet, reproduction, and absence of natural predators for its biological control (;Lima & Guilherme, 2018;Onyshi et al, 2018;Eduvirgem & Ferreira, 2020;Silva et al, 2020) The humid and shaded climatic conditions of the state of Amapá favor its occurrence, since this species reproduces easily in environments with these characteristics (Andreazzi et al, 2017;Alves et al, 2017a;Eduvirgem & Ferreira, 2020). In Macapá, the capital of Amapá, the incidence has been observed in almost all neighborhoods of the city and in much of the municipalities.…”
Section: Introductionmentioning
confidence: 99%
“…According to Silva et al (2020), the presence of the Giant African snail has been reported in different environments, such as forests, capoeiras, caatingas, savannas, plantations, vegetable gardens, as well as in urban areas. In the Amazon, surveys show that its presence may be associated with the transport of this mollusc in accidental loads, denoting in an alert situation due to its high dispersal capacity, diet, reproduction, and absence of natural predators for its biological control (;Lima & Guilherme, 2018;Onyshi et al, 2018;Eduvirgem & Ferreira, 2020;Silva et al, 2020) The humid and shaded climatic conditions of the state of Amapá favor its occurrence, since this species reproduces easily in environments with these characteristics (Andreazzi et al, 2017;Alves et al, 2017a;Eduvirgem & Ferreira, 2020). In Macapá, the capital of Amapá, the incidence has been observed in almost all neighborhoods of the city and in much of the municipalities.…”
Section: Introductionmentioning
confidence: 99%